ROMAN MILITARY INSCRIPTIONS FROM CELEIA AND ITS SURROUNDINGS - Visočnik, Julijana (Arheološki vestnik, 2008)
The author presents military inscriptions from Celeia and its surroundings except the inscriptions of beneficiarii; they are listed only in a table since they were analysed elsewhere. The inscriptions are collected in a catalogue (division town – ager). In the commentary they are analysed according to the military functions and units attested on them. The author outlines vari-ous other peculiarities: names, iconography, linguistic and other characteristics. The majority of the military inscriptions from Celeia are funerary monuments; there are only three votive altars and two honorific slabs. Many of the Celeian soldiers served in the legion II Italica, the only Norican legion. The inscriptions mostly attest common soldiers and veterans but praetorians and centurions are also documented.